Efek Bekam Basah terhadap Kualitas Hidup Penderita Hipertensi Primer - Nurhayani Nurhayani; Dwi Pudjanarko; Suhartono Suhartono; Nurahmi Nurahmi (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
ABSTRACTBackground: Primary hypertension is a chronic disease with the potential for complications, death, and very high medical costs. It is estimated that cases will reach 1.5 billion in 2025 if no appropriate interventions are found to suppress its growth. Wet cupping has been shown to have an effect on reducing blood pressure in patients with hypertension, but clinical analysis that supports this fact, including measurement of changes in the scores of patients’ quality of life, is still lacking.Methods: This study used a quasi-experimental method. The sample is patients with primary hypertension who consume antihypertensives regularly and are 35-64 years old. Scores of respondents' quality of life were measured before and after the intervention using the SF36 questionnaire. Data were analyzed using t test and Wilcoxon-Mann-Whitney test.Results: It was found that the mean score of quality of life in the treatment group increased by 14.40 ± 19.16 with a p value of 0.009. On the other hand, the control group experienced a decrease of 0.465 ± 0.98 in score with a p value of 0.88.Conclusion: Wet cupping is effective in improving the quality of life of patients with primary hypertension.